Joint component and method of manufacturing the same

By filling Al and Fe alloy fillers in the spot welding area of ​​high-strength steel, combined with heat treatment and spot welding process optimization, the problem of hydrogen embrittlement cracking is solved, and hydrogen embrittlement resistance and safety improvement in corrosion environments is achieved.

CN115103923BActive Publication Date: 2025-02-07NIPPON STEEL CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180013532.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-13
Filing Date
2021-02-12
Publication Date
2025-02-07
Estimated Expiration
2041-02-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent hydrogen embrittlement and cracking of high-strength steels in corrosive environments, especially in spot welding areas, resulting in safety and durability problems.

Method used

By filling the alloy filler containing Al and Fe around the spot welding area of ​​the steel member, and optimizing through heat treatment and spot welding process, a bonding component with excellent hydrogen embrittlement resistance is formed.

Benefits of technology

It significantly improves hydrogen embrittlement resistance in corrosive environments, ensures the safety and durability of high-strength steel, and is suitable for applications in automobiles and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115103923B_ABST
    Figure CN115103923B_ABST
Patent Text Reader

Abstract

The present invention relates to a joint component, comprising a first steel member, a second steel member, and a spot welding area for joining the first steel member and the second steel member, wherein the first steel member comprises a steel plate substrate having a predetermined chemical composition and a coating having a thickness of 25 μm or more formed on the surface of the steel plate substrate and containing Al and Fe, and in a cross section in the thickness direction of the first steel member and the second steel member including the spot welding area, a filler containing Al and Fe is present in a gap between the first steel member and the second steel member around the spot welding area, and the cross-sectional area of ​​the filler in the cross section is 3.0×10 4 μm 2 The gap within a range of 100 μm from the end of the plastic metal ring zone formed around the spot welding zone has a filling rate of 80% or more and includes the first region and the second region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a joining component and a method for manufacturing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2020-022754 filed on February 13, 2020, the contents of which are cited here. Background Art

[0003] In the automotive field, the use of steel sheets with higher tensile strength (high-strength steel sheets) is expanding in order to improve both fuel efficiency and collision safety, against the backdrop of recent stricter environmental regulations and collision safety standards. However, as the strength increases, the press formability of the steel sheets decreases, making it difficult to manufacture products with complex shapes.

[0004] Specifically, with the increase in strength, the ductility of the steel sheet decreases, and the problem of fracture occurs at the high processing position when processed into a complex shape. In addition, with the increase in the strength of the steel sheet, the residual stress after processing also causes rebound and wall warping, thereby deteriorating the dimensional accuracy. Therefore, it is not easy to process a steel sheet with high strength, especially a tensile strength of more than 780MPa, into a product with a complex shape by press forming. If it is not press forming but roll forming, it is easy to process a high-strength steel sheet, but its application is limited to parts with the same cross-section in the longitudinal direction.

[0005] Therefore, in recent years, hot stamping technology has been used as a technology for press-forming difficult-to-form materials such as high-strength steel sheets, as disclosed in, for example, Patent Documents 1 to 3. Hot stamping technology refers to a hot forming technology that heats the material to be formed and then forms it.

[0006] In this technology, the material is heated before being formed. Therefore, during forming, the steel material is soft and has good formability. As a result, even high-strength steel plates can be formed into complex shapes with high precision. In addition, in hot stamping technology, since quenching is performed while forming by the press working die, the formed steel component has sufficient strength.

[0007] For example, Patent Document 1 discloses that a steel member having a tensile strength of 1400 MPa or more after forming can be obtained by hot stamping technology.

[0008] In recent years, countries around the world have set higher CO2 reduction targets, and automobile companies are working to reduce fuel consumption based on collision safety considerations. Not only gasoline vehicles, but also rapidly developing electric vehicles need to protect not only passengers from collisions, but also batteries from collisions. In addition, in order to offset the increase in weight, further high strength is required for its materials. For example, in steel components used in automobiles, hot stamping components with higher strength than the 1.5GPa (1500MPa) currently used as steel components formed by hot stamping are required.

[0009] However, most metal materials deteriorate in many properties as they become stronger, especially in terms of hydrogen embrittlement sensitivity. It is known that in steel components, if the tensile strength reaches 1.2 GPa or more, the hydrogen embrittlement sensitivity increases, and there are cases of hydrogen embrittlement cracking in bolt steels that have been promoted to high strength before the automotive field. Therefore, there is a concern that the hydrogen embrittlement sensitivity will further increase in hot stamping components with a tensile strength exceeding 1.5 GPa.

[0010] Steel components used in automobiles are at risk of hydrogen embrittlement cracking due to hydrogen generated by steel corrosion during use. As mentioned above, the hydrogen embrittlement sensitivity of steel is very high, especially in the strength range exceeding 1.5 GPa, so it can be considered that hydrogen embrittlement can also occur through trace amounts of hydrogen generated by slight corrosion. However, it is difficult to completely prevent steel corrosion in automobile design. Therefore, in order to further reduce the weight of the vehicle body, hot stamping components exceeding 1.5 GPa are applied to the vehicle body, and for this purpose, the risk of hydrogen embrittlement cracking needs to be fully reduced.

[0011] When using a car, the spot weld area is particularly prone to hydrogen embrittlement. There are three main reasons why the spot weld area is particularly prone to hydrogen embrittlement. Specifically, the spot weld area is prone to hydrogen embrittlement because (i) corrosion is easy to occur in the spot weld area, (ii) stress is generated in the spot weld area when welding parts with poor dimensional accuracy, and (iii) the structure of the melted and solidified part such as the spot weld area is coarse and easy to embrittle. In other words, the main causes of hydrogen embrittlement in the spot weld area, namely the generation of hydrogen, the addition of stress, and the limit of the material are all under more stringent conditions than the stable part of the base material.

[0012] If the above (i) is supplemented, it is difficult to thoroughly perform chemical conversion treatment and painting on the parts where the steel plates (or components) are overlapped and welded, and if gaps exist due to poor dimensions, a large amount of hydrogen will be generated due to the expansion of local corrosion (gap corrosion reaction).

[0013] Regarding high-strength steel materials with a tensile strength exceeding 1.5 GPa, for example, Patent Document 2 discloses a press-formed product formed by hot pressing with excellent toughness and a tensile strength of 1.8 GPa or more. Patent Document 3 discloses a steel material having a very high tensile strength of 2.0 GPa or more, and thus good toughness and ductility. Patent Document 4 discloses a steel material having a relatively high tensile strength of 1.8 GPa or more, and thus good toughness. Patent Document 5 discloses a steel material having a very high tensile strength of 2.0 GPa or more, and thus good toughness.

[0014] However, in Patent Documents 2 to 5, the countermeasures for hydrogen embrittlement resistance, especially for hydrogen embrittlement of spot welds that may become embrittled in a corrosive environment, are not sufficient. Therefore, although the steel materials of Patent Documents 2 to 5 have a tensile strength exceeding 1.5 GPa, they are sometimes not able to fully meet the requirements for safety when used as automobile components.

[0015] Regarding high-strength steel materials having spot welding areas, for example, Patent Documents 6 to 8 disclose spot welding methods that can suppress electrode contamination of aluminum-plated steel sheets and generation of welding dust.

[0016] However, in any patent document, countermeasures against hydrogen embrittlement in spot welds of high-strength steels are insufficient, and in the application of high-strength steels having a tensile strength exceeding 1.5 GPa in automobile components, demands for higher safety are sometimes not adequately addressed.

[0017] Prior art literature

[0018] Patent Literature

[0019] Patent Document 1: Japanese Patent Application Publication No. 2002-102980

[0020] Patent Document 2: Japanese Patent Application Publication No. 2012-180594

[0021] Patent Document 3: Japanese Patent Application Publication No. 2012-1802

[0022] Patent Document 4: International Publication No. 2015 / 182596

[0023] Patent Document 5: International Publication No. 2015 / 182591

[0024] Patent Document 6: Japanese Patent Application Publication No. 2006-212649

[0025] Patent Document 7: Japanese Patent Application Publication No. 2011-167742

[0026] Patent Document 8: Japanese Patent Application Publication No. 2004-2932 Summary of the invention

[0027] Problems to be solved by the invention

[0028] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a joined component having a spot welding area and having excellent hydrogen embrittlement resistance in a corrosive environment, and a method for manufacturing the same.

[0029] Means for solving problems

[0030] The present invention is conceived to provide the following joining component and a method for manufacturing the same.

[0031] (1) One aspect of the present invention relates to a joined component comprising a first steel member, a second steel member, and a spot welding zone for joining the first steel member and the second steel member, wherein the first steel member comprises a steel plate substrate having a chemical composition, in mass%, of C: 0.25 to 0.65%, Si: 0.10 to 1.00%, Mn: 0.30 to 1.50%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, Ti: 0.010 to 0.100%, B: 0.0005 to 0.0100%, Mo: 0 to 1.00%, Cu: 0 to 1.00%, Ni: 0 to 1.00%, Cr: 0 to 1.00%, Nb: 0-0.10%, V: 0-1.00%, Ca: 0-0.010%, Al: 0-1.00%, Sn: 0-1.00%, W: 0-1.00%, Sb: 0-1.00%, Zr: 0-1.00% and REM: 0-0.30%, the remainder containing Fe and impurities; and a coating formed on the surface of the steel plate substrate, containing Al and Fe, with a thickness of 25 μm or more; in a cross section of the first steel member and the second steel member in the thickness direction including the spot welding area, a filler containing Al and Fe is present in the gap between the first steel member and the second steel member around the spot welding area; the filler has a cross-sectional area of ​​3.0×10 4 μm 2 The invention relates to a method for manufacturing a spot welding area of ​​the present invention, wherein the filler comprises a first region which contains, by mass%, Al: 15% to 35%, Fe: 55% to 75%, and Si: 4% to 9%, and a second region which contains, by mass%, Al: 35% to 55%, Fe: 40% to 55%, and Si: 1% to 4%.

[0032] (2) In the joined component described in (1) above, the chemical composition of the steel plate substrate of the first steel member contains, in mass %, one or more of Mo: 0.10-1.00%, Cu: 0.10-1.00%, and Ni: 0.10-1.00%, the first region may further contain 0.25% or more of one or more of Mo, Cu, and Ni in total, and the second region may further contain 0.15% or more of one or more of Mo, Cu, and Ni in total.

[0033] (3) In the bonding member described in (2) above, the average Feret diameter of the second region may be set to 30 μm or less.

[0034] (4) Another embodiment of the present invention relates to a method for manufacturing a joined component, comprising: a heat treatment step, wherein a steel member is obtained by heating a coated steel plate at a temperature increase rate of 1.0 to 1000°C / sec to a temperature of Ac3 point to (Ac3 point + 300)°C, and cooling the coated steel plate to a temperature of less than Ms point at a temperature greater than an upper critical cooling rate, wherein the coated steel plate comprises: a steel plate having a chemical composition, in mass %, of C: 0.25 to 0.65%, Si: 0.10 to 1.00%, Mn: 0.30 to 1.50%, P: less than 0.050%, S: less than 0.0100%, N: less than 0.010%, Ti: 0.0 10~0.100%, B: 0.0005~0.0100%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1.00%, Cr: 0~1.00%, Nb: 0~0.10%, V: 0~1.00%, Ca: 0~0.010%, Al: 0~1.00%, Sn: 0~1.00%, W: 0~1.00%, Sb: 0~1.00%, Zr: 0~1.00% and REM: 0~0.30%, the remainder includes Fe and impurities, and a coating, which is formed on the surface of the steel plate, contains Al, and the adhesion amount is 50g / m 2 The invention relates to a method of manufacturing a steel member having a heat treatment process and a second steel member which is an opposite material. The method comprises the steps of: spot welding the steel member after the heat treatment process and the second steel member which is an opposite material. The steel member and the second steel member are arranged in an overlapping manner with a gap of 50 μm to 500 μm at least at a position where a powered electrode is pressed; the powered electrode is pressed at a hitting angle of 15 degrees or less and a pressure of 300 kgf or more for the steel member and an upslope of gradually increasing the amount of powered electricity is applied for more than 5 cycles using an AC power supply of 50 Hz or 60 Hz to form a weld nugget for joining.

[0035] (5) According to the method for manufacturing a joined part according to (4) above, the chemical composition of the steel plate may contain, in mass %, one or more of Mo: 0.10 to 1.00%, Cu: 0.10 to 1.00%, and Ni: 0.10 to 1.00%.

[0036] (6) In the method for manufacturing a joined component according to (5) above, in the spot welding step, an average cooling rate of 800 to 500° C. may be set to 500° C. / sec or more.

[0037] Effects of the Invention

[0038] According to the above aspects of the present invention, it is possible to provide a joined component having a spot weld area that is excellent in resistance to hydrogen embrittlement in a corrosive environment, and a method for manufacturing the same.

[0039] The joined component of the above aspect of the present invention has high strength and excellent hydrogen embrittlement resistance, and therefore contributes to improving fuel efficiency and collision safety when used in automobile parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic diagram showing an example of the joining member involved in this embodiment. DETAILED DESCRIPTION

[0041] The present inventors investigated the effects of the structure of the weld zone and the steel material as the raw material on these characteristics in order to obtain a joint component having a spot weld zone with high tensile strength and excellent hydrogen embrittlement resistance in a corrosive environment. As a result, the following findings were obtained.

[0042] Most of the raw materials used in the commonly manufactured hot stamping components are coated steel plates with excellent corrosion resistance applied to the surface of the steel plate by aluminum plating. If the coated steel plate is hot stamped, the Al in the surface coating and the Fe of the steel plate undergo an alloying reaction during heating, and a steel component (coated steel component) having a coating containing Al and Fe (hereinafter sometimes referred to as an Al-Fe coating) can be obtained. Most of the steel plates that are commonly used and have a tensile strength of about 1.5 GPa after hot stamping contain about 0.20 mass% C, and this C is used to ensure the strength after hot stamping. By spot welding the steel component and joining it with other components, a joined part can be obtained.

[0043] (a) In order to further reduce the weight of the vehicle body, the inventors have conducted detailed research on high-strength components that exceed 1.5 GPa (1500 MPa) after hot stamping by increasing the C content. As a result, it is known that by setting the C content to 0.25 mass % or more, ultra-high strength with a tensile strength exceeding 1.5 GPa can be obtained after a heat treatment including quenching such as hot stamping. On the other hand, there is a concern that with ultra-high strength exceeding 1.5 GPa, the hydrogen embrittlement sensitivity increases, and there is a risk of hydrogen embrittlement cracking due to hydrogen generated in the corrosive environment when the car is used. In particular, when the coated steel component is used as a joining part, since the spot welding area is melted once, the corrosion resistance formed by the aluminum plating cannot be guaranteed, and there is a risk of hydrogen embrittlement.

[0044] (b) The present inventors have studied a method for suppressing hydrogen embrittlement by preventing corrosion of spot welds, which are starting points of embrittlement, in a joint component formed of a coated steel member having a high strength exceeding 1.5 GPa and having an Al-Fe coating. As a result, it has been found that corrosion can be sufficiently prevented by coating the periphery of the weld with an alloy containing Al and Fe.

[0045] (c) The present inventors further investigated the hydrogen embrittlement resistance of a coated steel member having a tensile strength exceeding 1.5 GPa, and found a composition design and a structure design that are excellent in hydrogen embrittlement resistance.

[0046] Based on the above findings, the inventors have developed a joint component formed of a high-strength coated steel member with a tensile strength exceeding 1.5 GPa, which significantly improves the hydrogen embrittlement resistance in a corrosive environment by preventing corrosion of the spot weld zone, reducing the amount of hydrogen intrusion, and improving the hydrogen embrittlement resistance of the steel material. Such a joint component has high strength and low risk of hydrogen embrittlement, so it can be used more safely in a vehicle body.

[0047] Hereinafter, each element of a joining component according to an embodiment of the present invention (joining component according to the present embodiment) and a method for manufacturing the same will be described in detail.

[0048] (A)Joint parts

[0049] The joining member 1 according to this embodiment is as follows Figure 1 As shown, it includes a first steel member 11, a second steel member 12, and a spot welding area 21 for joining the first steel member 11 and the second steel member 12. The first steel member 11 is a coated steel member including a steel plate substrate 111 having a predetermined chemical composition and a coating (Al-Fe coating) 112 formed on the surface of the steel plate substrate 111 and containing Al and Fe.

[0050] In addition, in the joint component 1 according to the present embodiment, in the cross section in the thickness direction of the first steel member 11 and the second steel member 12 including the spot welding area 21, a filler 31 containing Al and Fe is present in the gap g formed between the first steel member 11 and the second steel member 12 around the spot welding area 21. The filler 31 includes a first region containing, by mass%, Al: 15% or more and less than 35%, Fe: 55% or more and less than 75%, and Si: 4% or more and less than 9%, and a second region containing, by mass%, Al: 35% or more and less than 55%, Fe: 40% or more and less than 55%, and Si: 1% or more and less than 4%.

[0051] In addition, the filler 31 has a cross-sectional area of ​​3.0×10 4 μm 2 The above-mentioned filling rate in the said gap g within the range of 100 micrometers from the end part of the plastic metal ring area formed around the said spot welding area 21 is 80% or more.

[0052] The following explains them respectively.

[0053] (A1) First steel member

[0054] As described above, the first steel member 11 included in the joined component 1 according to the present embodiment includes the steel plate base material 111 and the coating (Al—Fe-based coating) 112 containing Al and Fe formed on the surface of the steel plate base material 111 .

[0055] As described later, the first steel member 11 can be obtained by subjecting a coated steel sheet having a steel sheet substrate and an Al-based coating to a heat treatment accompanied by quenching such as hot stamping.

[0056] (A1-1) Steel plate substrate

[0057] The steel plate substrate 111 of the first steel member 11 of the joint component 1 according to the present embodiment has a predetermined chemical composition. Specifically, the chemical composition includes, by mass%, C: 0.25-0.65%, Si: 0.10-1.00%, Mn: 0.30-1.50%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, Ti: 0.010-0.100%, B: 0.0005-0.0100%, Mo: 0-1.00%, Cu: 0. ~1.00%, Ni: 0~1.00%, Cr: 0~1.00%, Nb: 0~0.10%, V: 0~1.00%, Ca: 0~0.010%, Al: 0~1.00%, Sn: 0~1.00%, W: 0~1.00%, Sb: 0~1.00%, Zr: 0~1.00% and REM: 0~0.30%, and the remainder includes Fe and impurities.

[0058] The reasons for limiting each element are as follows. Here, the chemical composition of the steel plate substrate 111 refers to the chemical composition of the portion of the first steel member 11 excluding the Al-Fe coating 112 on the surface (e.g., the position at 1 / 4 of the thickness from the surface of the steel plate substrate). Hereinafter, the % of the content is mass % unless otherwise specified.

[0059] C: 0.25~0.65%

[0060] C is an element that can improve the hardenability of steel and the strength of steel components obtained after quenching such as hot stamping. If the C content is less than 0.25%, it is difficult to ensure sufficient strength (more than 1.5 GPa) in the steel components after quenching. Therefore, the C content is set to 0.25% or more. The C content is preferably 0.28% or more.

[0061] On the other hand, if the C content exceeds 0.65%, the strength of the steel member after quenching increases too much, and the hydrogen embrittlement resistance decreases significantly. Therefore, the C content is set to 0.65% or less. The C content is preferably 0.60% or less.

[0062] Si: 0.10~1.00%

[0063] Si is an element effective for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. In order to obtain this effect, the Si content needs to be set to 0.10% or more. The Si content is preferably 0.35% or more.

[0064] On the other hand, if the Si content in the steel exceeds 1.00%, the heating temperature required for austenite transformation during heat treatment (quenching) increases significantly. As a result, the cost required for heat treatment sometimes increases, or ferrite remains during heating, causing the strength of the steel member to decrease. Therefore, the Si content is set to 1.00% or less. The Si content is preferably 0.60% or less.

[0065] Mn: 0.30~1.50%

[0066] Mn is a very effective element for improving the hardenability of steel and stably ensuring the strength after quenching. Mn is also an element that reduces the Ac3 point and promotes the low temperature of the quenching treatment temperature. However, if the Mn content is less than 0.30%, the effect is not sufficient. Therefore, the Mn content is set to 0.30% or more. The Mn content is preferably 0.40% or more.

[0067] On the other hand, if the Mn content exceeds 1.50%, the hydrogen embrittlement resistance of the steel member after quenching deteriorates. Therefore, the Mn content is set to 1.50% or less. The Mn content is preferably 1.30% or less, and more preferably 1.10% or less.

[0068] P: 0.050% or less

[0069] P is an element that reduces the hydrogen embrittlement resistance of steel components after quenching. In particular, if the P content exceeds 0.050%, the hydrogen embrittlement resistance decreases significantly. Therefore, the P content is limited to 0.050% or less. It is preferred to limit the P content to 0.005% or less.

[0070] Since the P content is preferably as small as possible, it may be 0%, but from the viewpoint of cost, it may be set to 0.001% or more.

[0071] S: 0.0100% or less

[0072] S is an element that reduces the hydrogen embrittlement resistance of steel components after quenching. In particular, if the S content exceeds 0.0100%, the hydrogen embrittlement resistance decreases significantly. Therefore, the S content is limited to 0.0100% or less. It is preferred to limit the S content to 0.0050% or less. Since the S content is preferably less, it can also be 0%, but from the perspective of cost, it can also be set to 0.0001% or more.

[0073] N: 0.010% or less

[0074] N is an element that reduces the hydrogen embrittlement resistance of steel components after quenching. In particular, if the N content exceeds 0.010%, coarse nitrides are formed in the steel, and the hydrogen embrittlement resistance is significantly reduced. Therefore, the N content is set to less than 0.010%. The lower limit of the N content does not need to be specifically limited, and it can also be 0%, but setting the N content to less than 0.0002% will increase the steelmaking cost, which is not economically preferred. Therefore, the N content can be set to more than 0.0002%, and can also be set to more than 0.0008%.

[0075] Ti: 0.010~0.100%

[0076] Ti is an element that suppresses grain growth by forming fine carbides while suppressing recrystallization when the steel plate is heated to a temperature above the Ac3 point, and has the effect of refining the austenite grains. Therefore, by containing Ti, the effect of improving the hydrogen embrittlement resistance of the steel component can be obtained. In addition, Ti is also an element that suppresses the consumption of B caused by the precipitation of BN by preferentially combining with N in the steel, and promotes the effect of improving hardenability brought by B described later. If the Ti content is less than 0.010%, the above-mentioned effect cannot be fully obtained. Therefore, the Ti content is set to more than 0.010%. The Ti content is preferably more than 0.015%.

[0077] On the other hand, if the Ti content exceeds 0.100%, the amount of TiC precipitated increases and consumes C, so the strength of the steel member after quenching decreases. Therefore, the Ti content is set to 0.100% or less. The Ti content is preferably 0.080% or less.

[0078] B: 0.0005~0.0100%

[0079] B is an important element that can dramatically improve the hardenability of steel even in a trace amount. In addition, B is an element that improves hydrogen embrittlement resistance by strengthening the grain boundaries by segregating at the grain boundaries, and is an element that inhibits the grain growth of austenite when the steel plate is heated. If the B content is less than 0.0005%, the above-mentioned effect may not be fully obtained. Therefore, the B content is set to 0.0005% or more. The B content is preferably 0.0010% or more.

[0080] On the other hand, if the B content exceeds 0.0100%, a large amount of coarse compounds will precipitate, which will reduce the hydrogen embrittlement resistance of the steel member. Therefore, the B content is set to 0.0100% or less. The B content is preferably 0.0080% or less.

[0081] In the chemical composition of the steel plate base material 111 included in the first steel member 11 of the joint part of the present embodiment, the portion other than the above elements, i.e., the remaining portion, may also contain Fe and impurities, but in order to improve various properties (hardenability, strength, hydrogen embrittlement resistance, deoxidation, corrosion resistance, etc.) of the steel member and the joint part including the steel member, it may further contain one or more elements selected from Mo, Cu, Ni, Cr, Nb, V, Ca, Al, Sn, W, Sb, Zr, and REM within the range shown below. These elements are arbitrary elements and do not necessarily have to be contained, so the lower limit is 0%.

[0082] Mo: 0~1.00%

[0083] Mo is a very effective element for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. In particular, by containing it in combination with the above-mentioned B, a synergistic effect of improving hardenability can be obtained. In addition, Mo can further improve corrosion resistance by being contained in the filler (Al-Fe system filler) formed around the spot welding area. Therefore, it is preferably contained. If the Mo content is less than 0.10%, these effects are not sufficient, so it is preferred that the Mo content is set to more than 0.10%, and more preferably set to more than 0.20%.

[0084] On the other hand, Mo has the effect of stabilizing iron carbides. If the Mo content exceeds 1.00%, coarse iron carbides will melt and remain when the steel plate is heated, and sometimes the hydrogen embrittlement resistance of the steel component after quenching will decrease. In addition, the cost increase is significant. Therefore, the Mo content when contained is set to 1.00% or less. The Mo content is preferably 0.80% or less.

[0085] Cu: 0~1.00%

[0086] Cu is an effective element for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. In addition, Cu is also an element that further improves corrosion resistance by being contained in the Al-Fe system filler formed around the spot welding area described later. Therefore, it is preferably contained. If the Cu content is less than 0.10%, these effects are not sufficient, so when containing Cu, it is preferably set to more than 0.10%. The Cu content is more preferably more than 0.20%.

[0087] On the other hand, if the Cu content exceeds 1.00%, the above-mentioned effect is saturated and the cost increases. Therefore, when Cu is contained, the Cu content is set to 1.00% or less. The Cu content is preferably 0.80% or less.

[0088] Ni: 0~1.00%

[0089] Ni is an effective element for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. In addition, Ni is an element that further improves corrosion resistance by being contained in the Al-Fe-based filler formed around the spot welding area. Therefore, it is preferably contained. If the Ni content is less than 0.10%, these effects are not sufficient, so when Ni is contained, it is preferably set to more than 0.10%. The Ni content is more preferably more than 0.20%.

[0090] On the other hand, if the Ni content exceeds 1.00%, the limit hydrogen content of the steel component decreases. In addition, the cost increases significantly. Therefore, the Ni content when Ni is contained is set to 1.00% or less. The Ni content is preferably 0.25% or less, and more preferably 0.20% or less.

[0091] Cr: 0~1.00%

[0092] Cr is an effective element for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. Therefore, it can also be contained. In order to obtain the above-mentioned effect, the Cr content is preferably 0.01% or more, more preferably 0.05% or more, and further preferably 0.08% or more.

[0093] On the other hand, if the Cr content exceeds 1.00%, the above-mentioned effect is saturated and the cost increases. In addition, since Cr has the effect of stabilizing iron carbides, if the Cr content exceeds 1.00%, when the steel plate is heated, coarse iron carbides melt and remain, and sometimes the hydrogen embrittlement resistance of the steel member after quenching is reduced. Therefore, the Cr content is set to 1.00% or less when contained. The Cr content is preferably 0.80% or less.

[0094] Nb: 0~0.10%

[0095] Nb is an element that forms fine carbides and improves the hydrogen embrittlement resistance of steel through its grain refinement effect. If the Nb content is less than 0.02%, the above effect may not be fully obtained. Therefore, in order to obtain the above effect, it is preferred that the Nb content is set to 0.02% or more. The Nb content is more preferably 0.03% or more.

[0096] On the other hand, if the Nb content exceeds 0.10%, carbides will coarsen and the hydrogen embrittlement resistance of the steel member will decrease. Therefore, when Nb is contained, the Nb content is set to 0.10% or less. The Nb content is preferably 0.08% or less.

[0097] V: 0~1.00%

[0098] V is an element that forms fine carbides and improves the hydrogen embrittlement resistance of steel components through its grain refinement effect and hydrogen trapping effect. Therefore, it may also be contained. In order to obtain the above-mentioned effects, it is preferred to set the V content to 0.01% or more, and more preferably to 0.10% or more.

[0099] On the other hand, if the V content exceeds 1.00%, the above-mentioned effect is saturated and the economic efficiency is reduced. Therefore, when V is contained, the V content is set to 1.00% or less.

[0100] Ca: 0~0.010%

[0101] Ca is an element that has the effect of miniaturizing inclusions in steel and improving the hydrogen embrittlement resistance of steel components after quenching. Therefore, it may be contained. When the above-mentioned effect is obtained, it is preferred to set the Ca content to 0.001% or more, and more preferably to 0.002% or more.

[0102] On the other hand, if the Ca content exceeds 0.010%, the effect is saturated and the cost increases. Therefore, when Ca is contained, the Ca content is set to 0.010% or less. The Ca content is preferably 0.005% or less, and more preferably 0.004% or less.

[0103] Al: 0~1.00%

[0104] Al is an element generally used as a deoxidizer for steel. Therefore, Al may be contained. In order to obtain the above-mentioned effect, the Al content is preferably set to 0.01% or more.

[0105] On the other hand, if the Al content exceeds 1.00%, the above-mentioned effect is saturated and the economic efficiency is reduced. Therefore, when Al is contained, the Al content is set to 1.00% or less.

[0106] Sn: 0~1.00%

[0107] Sn is an element that improves corrosion resistance in a corrosive environment. Therefore, Sn may be contained. In order to obtain the above-mentioned effect, the Sn content is preferably set to 0.01% or more.

[0108] On the other hand, if the Sn content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel member after quenching decreases. Therefore, when Sn is contained, the Sn content is set to 1.00% or less.

[0109] W: 0~1.00%

[0110] W is an effective element for improving the hardenability of steel and stably ensuring the strength of steel components after quenching. Therefore, it can also be contained. In addition, W is an element that improves corrosion resistance in a corrosive environment. In order to obtain the above effect, the W content is set to 0.01% or more.

[0111] On the other hand, if the W content exceeds 1.00%, the above-mentioned effect is saturated and the economic efficiency is reduced. Therefore, when W is contained, the W content is set to 1.00% or less.

[0112] Sb: 0~1.00%

[0113] Sb is an element that improves corrosion resistance in a corrosive environment. Therefore, it may be contained. In order to obtain the above-mentioned effect, it is preferable to set the Sb content to 0.01% or more.

[0114] On the other hand, if the Sb content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel member after quenching decreases. Therefore, the Sb content, when contained, is set to 1.00% or less.

[0115] Zr: 0~1.00%

[0116] Zr is an element that improves corrosion resistance in a corrosive environment. Therefore, it may be contained. In order to obtain the above-mentioned effect, the Zr content is preferably set to 0.01% or more.

[0117] On the other hand, if the Zr content exceeds 1.00%, the grain boundary strength decreases, and the hydrogen embrittlement resistance of the steel member after quenching decreases. Therefore, the Zr content, when contained, is set to 1.00% or less.

[0118] REM: 0~0.30%

[0119] REM is an element that, like Ca, has the effect of miniaturizing inclusions in steel and improving the hydrogen embrittlement resistance of steel components after quenching. Therefore, it may also be contained. In order to obtain the above-mentioned effect, it is preferred to set the REM content to 0.01% or more, and more preferably to 0.02% or more.

[0120] On the other hand, if the REM content exceeds 0.30%, the effect is saturated and the cost increases. Therefore, when REM is contained, the REM content is set to 0.30% or less. The REM content is preferably 0.20% or less.

[0121] Here, REM refers to 17 elements including Sc, Y, La, Nd and other lanthanoid elements, and the content of REM means the total content of these elements. REM is added to molten steel using, for example, Fe-Si-REM alloy, and the alloy may contain, for example, La, Nd, Ce, and Pr.

[0122] In the chemical composition of the steel plate base material 111 included in the first steel member 11 included in the joining component of the present embodiment, the remainder other than the above-mentioned elements contains Fe and impurities.

[0123] Here, the so-called "impurities" are components mixed in during industrial production of steel plates through raw materials such as ores and scraps, and various reasons during the production process, and mean components that are allowed within a range that does not adversely affect the characteristics of the joining component involved in this embodiment.

[0124] The chemical composition of the steel plate substrate 111 can be obtained by the following method.

[0125] The chemical composition can be obtained by averaging the contents obtained by performing element analysis by a common method such as ICP in the thickness direction of the steel plate substrate 111 at a position 1 / 4 of the thickness from the surface.

[0126] Internal structure of steel plate substrate 111

[0127] The internal structure (metal structure) of the steel plate substrate 111 of the first steel member 11 included in the joint component 1 according to the present embodiment is mainly composed of high-strength martensite. Preferably, 70% or more of the area fraction is martensite. More preferably, 80% or more of the area fraction is martensite. Martensite may be 100%.

[0128] The internal structure of the steel plate substrate 111 may contain one or more of retained austenite, bainite, ferrite and pearlite as the remainder other than martensite. Martensite includes not only primary martensite but also tempered martensite and autotempered martensite. The so-called autotempered martensite is tempered martensite generated during cooling during quenching without heat treatment for tempering, and is a structure generated by tempering martensite generated under the action of self-heating accompanying martensitic transformation.

[0129] The internal structure of the steel plate substrate 111 can be determined by the following method.

[0130] The area fraction of martensite (including tempered martensite and autotempered martensite) can be measured by a transmission electron microscope (TEM) and an electron beam diffraction device attached to the TEM. A measurement sample is cut from 1 / 4 of the plate width of the steel component (a position that is 1 / 4 of the plate width away from the end in the width direction) and 1 / 4 of the plate thickness of the steel plate substrate 111 (a position that is 1 / 4 of the plate thickness away from the surface in the plate thickness direction) as a thin film sample for TEM observation. The thin film sample is a sample cut from a cross section in a direction perpendicular to the rolling direction. In addition, the range of TEM observation is set to 400μm in terms of area. 2 range. The diffraction pattern of the electron beam of the thin film sample can distinguish between the body-centered cubic lattice, that is, martensite and bainite, and the residual austenite of the face-centered cubic lattice. Moreover, the iron carbide (Fe3C) in the martensite and bainite is found through the diffraction pattern, and the tissue fractions of martensite and bainite can be determined respectively by observing the precipitation morphology. Specifically, if the precipitation morphology is precipitation in three directions, it is judged to be martensite, and if it is a limited precipitation in one direction, it is judged to be bainite. The tissue fractions of martensite and bainite respectively measured by TEM can be measured in area %, but the steel component of this embodiment has an isotropic metal structure, so the area fraction value can be directly replaced by the volume fraction. In order to distinguish martensite and bainite, carbides are observed, but in this embodiment, it is stipulated that carbides are not included in the volume fraction of the structure.

[0131] When ferrite or pearlite exists as the remaining structure, it is easy to confirm it by optical microscope or scanning electron microscope. Specifically, a measurement sample is cut from 1 / 4 of the plate width of the steel member and 1 / 4 of the plate thickness of the steel plate substrate as an observation sample. The sample is a sample cut from a cross section in a direction perpendicular to the rolling direction. In addition, the observation range of the microscope is set to 40000μm in area. 2The cut sample was mechanically ground and then mirror polished. Then, ferrite and pearlite were exposed by etching with nitric acid ethanol etching solution, and the presence of ferrite or pearlite was confirmed by microscopic observation. The structure in which ferrite and cementite were arranged alternately in layers was pearlite, and bainite in which cementite was precipitated in granular form was identified.

[0132] (A1-2) covered

[0133] The first steel member 11 of the joining part involved in the present embodiment has a coating (Al-Fe coating) 112 containing Al and Fe on the surface of the above-mentioned steel plate substrate 111. In the present embodiment, the Al-Fe coating is a coating mainly composed of Al and Fe, preferably containing more than 70% by mass of Al and Fe in total. In addition, the Al-Fe coating can also be called a film, an alloyed plating layer, or an intermetallic compound layer. In addition to Al and Fe, the Al-Fe coating can further contain Si, Mg, Ca, Sr, Ni, Cu, Mo, Mn, Cr, C, Nb, Ti, B, V, Sn, W, Sb, Zr, REM, and Zn, and the remainder is impurities.

[0134] The thickness of the Al-Fe-based coating is preferably 25 μm or more. The upper limit of the thickness of the Al-Fe-based coating is not particularly limited, and may be 100 μm or less.

[0135] The chemical composition and thickness of the Al-Fe-based coating can be determined by cross-sectional scanning electron microscopy and electron probe microanalyzer (EPMA). Ten visual fields are observed and the average values ​​are used as the chemical composition and thickness of the coating.

[0136] (A2) Second steel member

[0137] In the joint component 1 according to the present embodiment, the second steel member 12 joined to the first steel member 11 via the spot welding area 21 is not particularly limited from the viewpoint of the hydrogen embrittlement resistance of the spot welding area 21. However, when the corrosion resistance of the joint component 1 is taken into consideration, it is preferably a coated steel member having an Al-Fe coating similar to the first steel member 11 described above.

[0138] (A3) Welding area

[0139] The joining component 1 involved in this embodiment has a joining portion (spot welding area 21) formed by spot welding, and the first steel member 11 and the second steel member 12 are joined by the spot welding area 21. The spot welding area 21 includes a nugget formed by spot welding. Around the nugget, a plastic metal ring area (annular portion of solid phase bonding) is sometimes formed. The size of the nugget of the spot welding area 21 of the joining component 1 involved in this embodiment is not particularly limited, but when the plate thickness is defined as t (mm), it is preferably in the direction parallel to the plate surface. above.

[0140] (A4) Filling

[0141] The joining component 1 according to the present embodiment has a filler 31 containing Al and Fe around the above-mentioned spot welding area 21. That is, in the cross section in the thickness direction of the first steel member 11 and the second steel member 12 including the spot welding area 21, the filler 31 containing Al and Fe exists between the first steel member 11 and the second steel member 12 around the spot welding area 21 (for example, a position within a range of 100 μm or less from the end of the nugget, or when the plastic metal ring area is formed, from the end of the plastic metal ring area).

[0142] The joining component 1 according to the present embodiment is configured to overlap the first steel member 11 and the second steel member 12 with a gap of 50 μm to 500 μm, as described later, and the first steel member 11 and the second steel member 12 are joined by spot welding by pressing the energized electrodes at a striking angle of 15 degrees or less and a pressure of 300 kgf or more. Figure 1 As shown, although the first steel member 11 and the second steel member 12 are joined in the spot welding area 21, there is a gap g between the first steel member 11 and the second steel member 12 around it. By filling the gap with the filler 31, the corrosion of the spot welding area 21 can be suppressed and the hydrogen embrittlement resistance can be improved. In order to suppress the corrosion of the spot welding area 21, the filler 31 needs to exist in a way to fill the gap g between the first steel member 11 and the second steel member 12. The cross-sectional area of ​​the filler 31 is 3.0×104μm 2The filler 31 is preferably 80% or more, and the gap within the range of 100 μm from the end of the plastic metal ring zone formed around the spot welding area is necessary. The filling rate is preferably 90% or more, and can also be 100%. When the cross-sectional area is small or the filling rate is small, the corrosion of the spot welding area cannot be fully suppressed. The filler 31 can obtain the effect as long as it fills the gap g between the first steel member 11 and the second steel member 12 as described above in at least one cross section in the thickness direction of the first steel member 11 and the second steel member 12 including the spot welding area 21, but if the gap g is filled as described above in all cross sections, the effect can be further improved, so it is preferred.

[0143] The filling 31 consists of regions with two chemical compositions.

[0144] The chemical composition of the first region includes, by mass%, Al: 15% or more and less than 35%, Fe: 55% or more and less than 75%, Si: 4% or more and less than 9%. Mo, Cu, and Ni may be further included as required. In this case, the total content of Mo, Cu, and Ni is preferably set to 0.25% or more by mass.

[0145] The chemical composition of the second region includes, by mass%, Al: 35% to 55%, Fe: 40% to 55%, Si: 1% to 4%. Mo, Cu, and Ni may be further included as required, in which case the total content of Mo, Cu, and Ni is preferably set to 0.15% by mass or more.

[0146] Such a filler can be obtained by welding the above-mentioned steel members (the first steel member 11 and the second steel member 12 ) as will be described later.

[0147] As the remainder of the chemical composition of the first region and the second region, other chemical components contained in the steel sheet base material and the coating may be contained.

[0148] In addition, it is preferable that the second region is finely dispersed in the filler 31. In this case, the corrosion resistance is further improved. The reason for this is considered to be as follows:

[0149] The second region has a higher Al content than the first region, so the sacrificial anode corrosion protection effect is higher than that of the first region. Therefore, when the filler is corroded, the second region is corroded preferentially compared to the first region. The second region is dispersed in the filler in a fine grid-like structure, so that the area that is preferentially corroded is expanded. Therefore, the finer the second region is dispersed in the filler, the higher the anti-corrosion effect of the filler.

[0150] Specifically, the second region is preferably dispersed in a fine size with an average Feret diameter of 30 μm or less. Since the second region is dispersed in a grid shape, its shape is diverse. Therefore, the size of the second region is determined by the Feret diameter. For the convenience of explanation, the method for measuring the size of the second region will be described later.

[0151] The cross-sectional area and filling rate of the filler 31 can be obtained by the following method.

[0152] A vertical cross section passing through the center of the weld is cut so that the cross section of the spot weld (the nugget and the plastic metal ring area) and the filler can be observed in the joined component 1, and the area of ​​the filler is calculated in the cross section. The cutting method is, for example, in accordance with JIS Z3139: 2009. Five or more specimens are cut under the same welding conditions, the cross-sectional area is calculated, and the average value is taken as the cross-sectional area of ​​the filler.

[0153] In addition, the proportion of the filler in the area other than the steel member is calculated from the terminal of the crimping part (plastic metal ring area) in the cross section to the gap part to 100 μm. Five or more specimens are cut under the same welding conditions, and the proportion is calculated, and the minimum value is taken as the filling rate of the filler.

[0154] The contents of Al, Fe, Si, Mo, Cu, and Ni contained in the filler 31 can be obtained by the following method.

[0155] A vertical section through the center of the weld is cut in such a way that the cross section of the spot weld (the nugget and the plastic metal ring zone) and the filler can be observed in the joint component 1. For this sample, a backscattered electron image is obtained using a scanning electron microscope, and an electron probe microanalyzer (EPMA) is used to perform point element analysis (beam diameter of less than 1 μm) on the two structures with different contrasts constituting the filler, thereby being able to determine the content of Al, Fe, Si, Mo, Cu, and Ni contained in the filler. During the measurement, 10 points of analysis are performed on the two structures of the first area that appears bright due to the high content of heavy elements, namely Fe, and the second area outside it, and the average value is taken as the content of Al, Fe, Si, Mo, Cu, and Ni contained in the filler.

[0156] The size of the second region included in the filler 31 can be obtained as follows.

[0157] A vertical section through the center of the weld is cut in such a way that the cross section of the spot weld (the nugget and the plastic metal ring zone) and the filler can be observed in the joint component 1. For this sample, a backscattered electron image is obtained using a scanning electron microscope. As described above, the second region can be judged by contrast. In addition, the size of the second region can be defined as the average value of the distance between parallel lines in the horizontal direction that sandwich the second region (horizontal Feret diameter) and the distance between parallel lines in the vertical direction that sandwich the second region (vertical Feret diameter). The so-called horizontal direction is the length direction of the joint component, and the so-called vertical direction is the plate thickness direction perpendicular to the length direction.

[0158] In the bonding member according to this embodiment, the second region often has an island shape surrounded by the first region. During measurement, the sizes of 15 island-shaped second regions surrounded by the first region are measured, and the average value is taken as the size of the second region contained in the filler.

[0159] (A5) Characteristics of joint parts

[0160] The joining component 1 of this embodiment prevents corrosion by controlling the filler 31 as described above, thereby reducing the intrusion of corrosion factors into the spot welding area 21. In addition, the joining component 1 of this embodiment has a high strength with a tensile strength exceeding 1.5 GPa and excellent hydrogen embrittlement resistance in a corrosive environment.

[0161] In this embodiment, the hydrogen embrittlement resistance in a corrosive environment can be evaluated by an exposure test in the actual use environment of the joint component or an accelerated corrosion test based on a CCT (combined cycle test). For example, CCT can be performed in accordance with the provisions of JASO standards M609 and M610, and the evaluation can be performed based on the number of cycles without fracture in the spot weld area.

[0162] The shape of the joint component 1 is not particularly limited. That is, the first steel member 11 and / or the second steel member 12 may be a flat plate or a formed body. Most of the hot-formed covered steel members are formed bodies, but in this embodiment, both the formed body and the flat plate are included and referred to as "covered steel members". In addition, the covered steel members may also be tailored property materials whose strength varies depending on the location.

[0163] (B) Coated steel sheet as raw material

[0164] Next, the coated steel plate (hereinafter sometimes referred to as the coated steel plate involved in the present embodiment) which is the raw material of the first steel member (coated steel member) included in the joint component involved in the present embodiment is described. The first steel member can be obtained by performing heat treatment using the coated steel plate described below as the raw material of the first steel member 11. The coated steel plate can also be used as the raw material of the second steel member 12.

[0165] The coated steel sheet according to the present embodiment includes a steel sheet having a predetermined chemical composition and a coating (Al-based coating) containing Al formed on the surface of the steel sheet.

[0166] (B1) Chemical composition of steel plate

[0167] The range of the chemical composition of the steel plate constituting the coated steel plate involved in this embodiment is the same as the chemical composition of the steel plate substrate 111 in the first steel member 11, and the reason for limitation is the same. Here, the chemical composition of the steel plate refers to the chemical composition of the portion other than the Al-based coating on the surface and the boundary region between the Al-based coating and the steel plate in the coated steel plate. For example, it can be obtained by taking a position 1 / 4 of the thickness from the surface of the steel plate in the thickness direction as a representative position and performing elemental analysis at this position using a common method such as ICP.

[0168] (B2)Covered

[0169] The coated steel sheet involved in this embodiment has a coating containing Al (hereinafter referred to as Al-based coating) on ​​the surface of the steel sheet. The so-called Al-based coating is a coating mainly composed of Al, preferably containing more than 40% Al. Al-based coating is also called a film or a plating layer. In addition to Al, the Al-based coating may further contain Si, Mg, Ca, Sr, Ti, Zn, Sb, Sn, Ni, Cu, Co, In, Bi, and REM, and the remainder is impurities. Generally speaking, most of them contain about 10% Si.

[0170] The type of Al-based coating is not limited, and examples thereof include coatings formed by hot-dip plating, electroplating, thermal spraying, and the like.

[0171] The Al coating weight is preferably 50 g / m 2 The upper limit of the amount of Al-based coating is not particularly limited, and the amount of coating may be set to 150 g / m 2 the following.

[0172] The chemical composition and thickness of the coating can be determined by scanning electron microscope observation and electron probe microanalyzer (EPMA) of the cross section in the same manner as the coating of the first steel member.

[0173] (B3) Internal structure of steel plate

[0174] The internal structure (metal structure) of the steel plate of the coated steel plate involved in the present embodiment is not limited, but most of them are ferrite or pearlite. Under the conditions of the manufacturing method described below, bainite or martensite, residual austenite is sometimes contained. The above-mentioned martensite also includes tempered martensite and self-tempered martensite. The so-called self-tempered martensite is tempered martensite generated during cooling during quenching without heat treatment for tempering. It is generated by tempering the martensite produced on the spot under the action of heat generated by martensitic phase transformation. The so-called internal structure of the steel plate is the structure of the steel plate except for the above-mentioned boundary portion.

[0175] The internal structure of the steel plate can be determined in the same manner as the internal structure of the steel plate base material described above.

[0176] (C) Method for manufacturing a joint component

[0177] Next, a method for manufacturing the joining member 1 according to the present embodiment will be described.

[0178] The joining member 1 according to the present embodiment can be obtained by subjecting the coated steel sheet according to the present embodiment as described above to a heat treatment described later to form a steel member, and then joining a plurality of steel members including the steel member by spot welding.

[0179] Hereinafter, each step will be described.

[0180] <Heat treatment process>

[0181] Heat treatment is performed, for example, under the following conditions: the coated steel sheet obtained by the above method is heated to Ac3 point to (Ac3 point + 300)°C at a heating rate of 1.0 to 1000°C / sec, and then cooled to below Ms point at a cooling rate greater than the upper critical cooling rate.

[0182] If the heating rate is lower than 1.0°C / sec, the productivity of the heat treatment decreases, which is not preferable. On the other hand, if the heating rate exceeds 1000°C / sec, a mixed crystal structure is formed, and the limit hydrogen amount decreases, which is not preferable.

[0183] In addition, if the heat treatment temperature is lower than the Ac3 point, ferrite remains after cooling, and the strength is insufficient, which is not preferred. On the other hand, if the heat treatment temperature exceeds the Ac3 point + 300°C, the structure becomes coarse and the limit hydrogen content decreases, which is not preferred.

[0184] The so-called upper critical cooling rate is the minimum cooling rate at which ferrite and pearlite are not precipitated in the structure and martensite is generated by supercooling austenite. If cooling is performed at a cooling rate lower than the upper critical cooling rate, ferrite and pearlite are generated, resulting in insufficient strength.

[0185] During heating, the temperature may be maintained within a range of ±10° C. of the heating temperature for 1 to 300 seconds.

[0186] Furthermore, after cooling, a tempering treatment may be performed in a temperature range of about 100 to 600° C. in order to adjust the strength of the steel member.

[0187] The Ac3 point, Ms point and upper critical cooling rate can be measured by the following method.

[0188] A long test piece of 30 mm in width and 200 mm in length is cut from a steel plate having the same chemical composition as the steel plate of the coated steel plate according to the present embodiment, and the test piece is heated to 1000°C at a heating rate of 10°C / second in a nitrogen atmosphere, kept at this temperature for 5 minutes, and then cooled to room temperature at various cooling rates. The cooling rate can be set from 1°C / second to 100°C / second at intervals of 10°C / second. The Ac3 point is determined by measuring the thermal expansion change of the test piece during heating at this time.

[0189] In addition, in each test piece cooled at the above cooling rate, the minimum cooling rate at which no precipitation of the ferrite phase occurs is taken as the upper critical cooling rate. The thermal expansion change during cooling at a cooling rate above the upper critical cooling rate is measured, and the phase transformation start temperature at this time is taken as the Ms point.

[0190] Here, during the above series of heat treatments, after heating to the temperature range of Ac3 point to (Ac3 point + 300) ° C, until cooling to the Ms point, that is, while implementing the cooling process at a rate above the upper critical cooling rate, hot forming such as hot stamping can also be implemented. As hot forming, bending, drawing, bulging, hole expansion and flange forming can be listed. In addition, as long as there is a means for cooling the steel plate at the same time or immediately after forming, the present invention can also be applied to forming methods other than press forming, such as roll forming. If the above-mentioned thermal process is followed, repeated hot forming can also be implemented.

[0191] As described above, in the present embodiment, the first steel member 11 and the second steel member 12 of the “joined component 1” include both the case where they are formed into a molded body by hot forming and the case where they are formed into a flat plate by only performing a heat treatment.

[0192] Furthermore, as the first steel member 11 , by hot forming or heat treating a portion of the coated steel sheet serving as a raw material, a coated steel member having regions with different strengths can be obtained.

[0193] The above series of heat treatments can be performed by any method, for example, high frequency heating, electric heating, infrared heating, furnace heating, etc. Cooling can also be performed by water cooling, mold cooling, etc.

[0194] <Spot welding process>

[0195] In the spot welding process, the coated steel member (first steel member) and the steel member (second steel member) that have been subjected to the above heat treatment are arranged with a gap of 50 μm to 500 μm in the middle at least at the position where the energized electrode is pressed, and the energized electrode is pressed with a strike angle of 15 degrees or less and a pressure of 300 kgf or more for the coated steel member and the steel member that is the welding counterpart. After applying an upward slope with a gradually increasing amount of energized electricity for more than 5 cycles using a 50 Hz or 60 Hz AC power supply, the coated steel member and the welding counterpart are joined by forming a weld nugget. The spot welding method, its apparatus, and electrode are not limited, and for example, the contents described in JIS Z3001-6: 2013, JIS C9305: 2011, and JIS C9304: 1999 can be used. If it is a single-phase AC type, it is 50 Hz or 60 Hz, and the electrode is an electrode with a front end diameter of 6 mm or more, and the welding time is preferably more than 10 cycles.

[0196] Furthermore, when controlling the distribution state of the second region in the filler, it is preferable to control the cooling conditions of the spot welding.

[0197] Each condition is described below.

[0198] The gap between the coated steel member and the corresponding steel member: 50μm to 500μm

[0199] In spot welding of joined parts, the Al-Fe coating on the surface is melted and spouted out to the periphery of the weld zone to form a filler. If a gap of 50 μm or more is not set between the coated steel member and the welding counterpart at least at the position where the energized electrode is pressed, the spouting of the molten Al-Fe alloy to the periphery of the weld zone is stagnant, and the cross-sectional area of ​​the filler may be less than 3.0×10 4 μm 2 , and is therefore not preferred.

[0200] On the other hand, if the interval exceeds 500 μm, the filling rate of the filler may be less than 80%, which is not preferable.

[0201] Attack angle below 15 degrees

[0202] The so-called strike angle of the powered electrode is the contact angle between the powered electrode and the coated steel sheet. The angle between the axial direction of the powered electrode and the direction parallel to the surface of the coated steel sheet is set to 0, which indicates the resulting deviation. If the strike angle exceeds 15 degrees, the molten Al-Fe alloy will be unevenly ejected around the weld zone, and the filler cannot be uniformly formed around the weld zone. Sometimes the filling rate is less than 80%, so it is not preferred. In this case, corrosion cannot be fully prevented, and the hydrogen embrittlement resistance in a corrosive environment is reduced, so it is not preferred. The strike angle is preferably less than 10 degrees.

[0203] Pressure over 300kgf

[0204] By applying pressure between the welding electrodes, the Al-Fe coating contacts the welding counterpart, and the coated Al-Fe alloy is ejected to the periphery of the weld zone in accordance with the contact area. If the pressure is less than 300 kgf, the contact area between the Al-Fe coating in the coated steel plate and the welding counterpart is insufficient, so a sufficient amount of Al-Fe alloy cannot be ejected to the periphery of the weld zone, and sometimes the cross-sectional area of ​​the filler around the spot weld zone is less than 3.0×10 4 μm 2 The pressure is preferably 400 kgf or more.

[0205] Upslope: 5 or more cycles

[0206] The so-called upslope is the current reaching cycle until the steel plate base material is melted to form a nugget, during which the Al-Fe coating on the surface of the coated steel plate melts and spits out to the periphery of the weld zone. If the upslope is less than 5 cycles, the surface Al-Fe alloy melts rapidly and enters the nugget, which sometimes makes the amount of Al, Si, Mo, Cu, and Ni contained in the first region or the second region of the filler insufficient, so it is not preferred.

[0207] Cooling rate of spot welding: 800-500℃ average cooling rate is 500℃ / sec or more

[0208] It is preferable to increase the cooling rate during spot welding cooling (cooling after forming a nugget) to finely disperse the second region in the filler. It is believed that the reason is that when the filler (molten material that becomes the filler) ejected to the periphery of the weld zone during welding is cooled, if the cooling rate is 500°C / sec or more, the preferential solidification of the first region containing more Fe and having a higher solidification point is promoted, and the cohesion and coarsening can be suppressed by dividing the second region.

[0209] For example, by setting the holding time of the electrode to 5 cycles or more, the cooling medium (compressed air or cooling water) is directly flowed into the gap between the steel plates to promote cooling, thereby obtaining the above cooling rate. In order to obtain the above cooling rate, the number of holding cycles of the electrode is particularly preferably 5 cycles or more. The more the number of holding cycles, the better, but considering the manufacturing efficiency, it is preferably 10 cycles or less.

[0210] If the cooling rate is too fast, defects (shrinkage cavities) of the weld nugget and the filler will occur. From this point of view, it is preferably 5000° C. / sec or less.

[0211] The cooling rate of spot welding can be calculated by the following method. An R-type thermocouple is deposited between the coated steel member and the welding counterpart at a position within 10 mm from the welding center, and the temperature change during welding is measured. In this embodiment, the average cooling rate of 800 to 500°C, at which the filler solidifies and the temperature is relatively stable, is used as the cooling rate of spot welding.

[0212] (D) Method for manufacturing coated steel sheet

[0213] The coated steel plate suitable as the material of the first steel member included in the joining component according to the present embodiment can be produced by adopting a production method including the steps shown below, for example.

[0214] Manufacturing method

[0215] (i) Slab preparation process of melting steel having the above chemical composition and then manufacturing a slab by casting

[0216] (ii) A hot rolling step of hot-rolling the obtained slab to form a hot-rolled steel sheet

[0217] (iii) Coiling process of hot-rolled steel sheet

[0218] (iv) A hot rolled steel sheet annealing step of annealing the hot rolled steel sheet after the coiling step as necessary

[0219] (v) a cold rolling process in which the hot-rolled steel sheet is descaled after the coiling process or the hot-rolled steel sheet annealing process as required, and then cold-rolled to form a cold-rolled steel sheet.

[0220] (vi) Annealing step of annealing the hot-rolled steel sheet or the cold-rolled steel sheet to form an annealed steel sheet as required

[0221] (vii) Coating step of applying Al-based coating to a hot-rolled steel sheet, a cold-rolled steel sheet or an annealed steel sheet to form a coated steel sheet

[0222] Hereinafter, each step will be described.

[0223] <Slab preparation process>

[0224] In the slab preparation process, steel having the above chemical composition is melted and cast to produce a slab for hot rolling. For example, a slab produced by melting molten steel having the above chemical composition in a converter or an electric furnace and then continuously casting can be used. Ingot casting, thin slab casting, etc. may be used instead of continuous casting.

[0225] <Hot rolling>

[0226] In the hot rolling process, the slab is heated, rough-rolled, descaled as necessary, and finally finish-rolled. The hot rolling conditions are not limited.

[0227] <Coiling process>

[0228] In the coiling process, the hot rolled steel sheet is coiled at a temperature of, for example, 800° C. or less. If the coiling temperature exceeds 800° C., the steel sheet is coiled with almost no phase transformation, and phase transformation occurs in the coil, which may result in poor coil shape.

[0229] <Hot-rolled sheet annealing process>

[0230] In the hot rolled sheet annealing process, the hot rolled steel sheet is annealed at 450-800° C. for 5 hours or more in an atmosphere containing 80% by volume or more nitrogen or in an air atmosphere. Hot rolled sheet annealing is not necessarily required, but hot rolled sheet annealing is preferred because it can soften the hot rolled steel sheet and reduce the load in the next process, namely the cold rolling process.

[0231] <Cold rolling process>

[0232] In the cold rolling process, the hot rolled steel sheet after the hot rolled sheet annealing process (the hot rolled steel sheet after the coiling process when the hot rolled sheet annealing process is not performed) is descaled and then cold rolled to form a cold rolled steel sheet. Descaling and cold rolling are not necessarily performed, but when cold rolling is performed, from the viewpoint of ensuring good flatness, the cumulative reduction rate in cold rolling is preferably set to 30% or more. On the other hand, in order to avoid the rolling load becoming too large, the cumulative reduction rate in cold rolling is preferably set to 80% or less.

[0233] The descaling method is not particularly limited, but is preferably pickling. In addition, when pickling is performed, it is preferred that only the iron oxide scale is removed by hydrochloric acid pickling or sulfuric acid pickling.

[0234] <Annealing process>

[0235] In the annealing process before coating, the hot rolled steel sheet or the cold rolled steel sheet is annealed in a temperature range of 700 to 950° C. Annealing before coating is not necessarily required, but the annealing process is preferred because it can soften the cold rolled steel sheet and facilitate the sheet passing in the next process, i.e., the coating process.

[0236] <Coating process>

[0237] In the coating process, Al coating is performed to form Al coating on the surface of the steel plate (hot rolled steel plate after the coiling process, hot rolled steel plate after the hot rolled plate annealing process, cold rolled steel plate after the cold rolling process, or annealed steel plate after the annealing process) to form a coated steel plate. The Al coating method is not particularly limited, and electroplating, vacuum evaporation, coating, spraying, etc. can be used, represented by hot dip plating. The most popular method in industry is hot dip plating.

[0238] During hot-dip plating, Fe is often mixed into the plating bath as an impurity in addition to Al. In addition, in addition to the above elements, Si, Ni, Mg, Ti, Zn, Sb, Sn, Cu, Co, In, Bi, Ca, mixed rare earth, etc. may be further contained in the plating bath as long as Al is contained at least 70%.

[0239] When hot-dip galvanizing is performed, the annealed steel sheet after the annealing step may be cooled to room temperature and then heated again before galvanizing, or the steel sheet may be cooled to 650 to 750° C. near the galvanizing bath temperature after annealing and hot-dip galvanizing may be performed without cooling to room temperature.

[0240] There are no particular restrictions on the pretreatment and post-treatment of the Al-based coating, and pre-coating or solvent coating, alloying treatment, temper rolling, etc. can be performed. As an alloying treatment, for example, annealing can be performed at 450 to 800°C. In addition, as a post-heat treatment, temper rolling is useful for shape adjustment, etc., and for example, a reduction of 0.1 to 0.5% can be performed.

[0241] Example

[0242] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0243] First, when manufacturing a coated steel plate, a coated steel member, and a joined component, steel having the chemical composition shown in Table 1 is melted to obtain a slab for hot rolling.

[0244]

[0245] <Example 1>

[0246] The obtained slab was hot rolled and coiled at a temperature below 800°C to form a hot rolled steel sheet with a thickness of 2.7 mm. The hot rolled steel sheet was cold rolled to form a cold rolled steel sheet with a thickness of 1.6 mm. The cold rolled steel sheet was aluminum plated to obtain a coated steel sheet with an Al coating.

[0247] The chemical composition at a position 1 / 4 of the plate thickness from the surface in the plate thickness direction of the coated steel plate is the same as that of the slab.

[0248] Heat the coated steel plate at the heating rates and heating temperatures shown in Table 2A, Table 2D, and Table 2G, hold for 60 seconds within the range of ±10 °C of the heating temperature, and perform heat treatment to cool below the Ms point at the average cooling rates shown in Table 2A, Table 2D, and Table 2G, thereby obtaining a coated steel member.

[0249] The chemical composition at a position 1 / 4 of the plate thickness from the surface in the plate thickness direction of the steel plate substrate of the coated steel member is the same as that of the slab.

[0250] Cut out the obtained coated steel member, perform SEM observation and tensile test according to the following method, and evaluate the thickness and tensile strength of the Al-Fe based coating. The evaluation results are shown in Table 2A, Table 2D, and Table 2G.

[0251] <Thickness of Al-Fe based coating>

[0252] Avoiding the end of the steel member, cut out a measurement specimen, observe the cross-section with a scanning electron microscope in 10 fields of view, measure the thickness of the Al-Fe based coating, and take its average value as the thickness of the Al-Fe based coating.

[0253] <Tensile strength>

[0254] The tensile test is carried out in accordance with the provisions of ASTM standard E8. After grinding the soaking part (the part more than 50 mm from the end) of the coated steel member to a thickness of 1.2 mm, collect a half-size plate-shaped test piece (parallel length: 32 mm, parallel part plate width: 6.25 mm) of ASTM standard E8 with the test direction parallel to the rolling direction. Then, perform a room temperature tensile test at a strain rate of 3 mm / min and measure the tensile strength (maximum strength). In this example, a case with a tensile strength exceeding 1500 MPa is evaluated as having a high strength.

[0255] Weld the steel members according to the spot welding conditions shown in Table 2A, Table 2D, and Table 2G: gap, impact angle, pressing force, upslope, and cooling rate, thereby obtaining a joined component. In this example, the welding corresponding materials are also set as the same steel members. The nugget diameter is 5.1 - 6.3 mm. The welding machine is a single-phase AC type (60 Hz power supply), and a current reaching the above-mentioned nugget diameter is applied for 20 cycles of welding time. The electrode uses an electrode made of alumina-dispersed copper with a front end diameter of 8 mmΦ, a dome-shaped radiation type.

[0256] In the obtained bonded parts, the cross-sectional area of ​​the filler, the filling rate, the content of Al, Fe, Si, Mo, Cu, and Ni, and the fracture resistance in CCT were evaluated by the following methods. The evaluation results are shown in Table 2B, Table 2C, Table 2E, Table 2F, Table 2H, and Table 2I.

[0257] <Cross-sectional area of ​​filler>

[0258] In such a way that the spot weld area (nugget and plastic metal ring area) and the cross section of the filler can be observed in the joined parts, a vertical cross section passing through the center of the weld is cut, and the area of ​​the filler is calculated in the cross section. Five or more specimens are cut under the same welding conditions, and the cross-sectional area is calculated, and the average value is taken as the cross-sectional area of ​​the filler.

[0259] <Fill Rate>

[0260] In order to observe the cross section of the spot welding area (nucleus and plastic metal ring area) and the filler in the joint part, a vertical cross section through the center of the welding point is cut, and the proportion of the filler in the area other than the steel member is calculated within a range of 100μm from the terminal of the crimping part (plastic metal ring area) in the cross section toward the gap. Cut more than 5 samples under the same welding conditions, calculate the proportion, and the minimum value is taken as the filling rate of the filler.

[0261] <Contents of Fe, Al, Si, Mo, Cu, and Ni in Fillers>

[0262] In such a way that the spot welding area (molten core and plastic metal ring area) and the cross-section of the filler can be observed in the joined parts, a vertical cross-section passing through the center of the welding point is cut, and a backscattered electron image is obtained for the sample using a scanning electron microscope. An electron probe microanalyzer (EPMA) is used to perform elemental analysis at 10 points (beam diameter of less than 1 μm) on two structures with different contrasts, and the average value is used as the content of Al, Fe, Si, Mo, Cu, and Ni contained in the filler.

[0263] <Size of the Second Region in the Filler>

[0264] In order to observe the cross section of the spot welding area (the nugget and the plastic metal ring area) and the filler in the joint part, a vertical cross section through the center of the welding point was cut. For this sample, a backscattered electron image was obtained using a scanning electron microscope. For two structures with different contrasts, the size of the island-shaped second area surrounded by the first area was measured. The size of the second area here is defined as the average value of the distance between parallel lines clamping the second area with parallel lines in the horizontal direction (horizontal Feret diameter) and the distance between parallel lines clamping the second area with parallel lines in the vertical direction (vertical Feret diameter). The so-called horizontal direction is the length direction of the joint part, and the so-called vertical direction is the plate thickness direction perpendicular to the length direction. During the measurement, the size of 15 island-shaped second areas surrounded by the first area was measured, and the average value was taken as the size of the second area contained in the filler.

[0265] <Fracturing cycle based on CCT>

[0266] The hydrogen embrittlement resistance in a corrosive environment was evaluated by an accelerated corrosion test based on CCT (combined cycle test). Specifically, a sample with a length of 100 mm and a width of 50 mm was collected from the joint component with the spot welding area as the center, and CCT was performed in accordance with the provisions of JASO standards M609 and M610, and the evaluation was performed based on the number of cycles without fracture in the spot welding area. CCT was implemented for 360 cycles. For samples that did not fracture after 360 cycles, a vertical section through the center of the welding point was cut, and the reduction rate of the cross-sectional area of ​​the filler before and after the test was measured. When the reduction rate was less than 10%, it was evaluated as being particularly excellent relative to the corrosive environment.

[0267]

[0268]

[0269]

[0270]

[0271]

[0272]

[0273]

[0274]

[0275]

[0276] As shown in Tables 2A to 2I, the inventive examples B1 to B67 that meet the scope of the present invention have good results in both organization and properties, but the comparative examples b1 to b26 that do not meet the scope of the present invention have poor strength (strength of the steel member that is the raw material) and hydrogen embrittlement resistance due to insufficient chemical composition or filler formation. In addition, when the filler contains Mo, Cu, and Ni, it is particularly excellent in corrosive environments.

[0277] Industrial Applicability

[0278] According to the present invention, a high-strength joint component having a spot weld zone with excellent hydrogen embrittlement resistance in a corrosive environment can be obtained. The joint component of the present invention is particularly suitable for use as a frame component of an automobile. Since the steel component of the present invention has high strength and excellent hydrogen embrittlement resistance, it helps to improve fuel efficiency and collision safety when used in automobile parts.

[0279] Explanation of symbols:

[0280] 1: Joining parts

[0281] 11: First steel member

[0282] 12: Second steel member

[0283] 21: Spot welding area

[0284] 31: Filler

[0285] 111: Steel plate substrate

[0286] 112: Al-Fe series coating

[0287] g: gap

Claims

1. A joining component comprising a first steel member, a second steel member, and a spot welding area for joining the first steel member and the second steel member, characterized in that: The first steel member comprises: The steel plate substrate has a chemical composition, expressed in mass%, of: C:0.25~0.65%、 Si: 0.10-1.00%, Mn: 0.30-1.50%, P: 0.050% or less, S: 0.0100% or less, N: 0.010% or less, Ti: 0.010~0.100%, B:0.0005~0.0100%、 Mo: 0-1.00%, Cu: 0-1.00%, Ni: 0-1.00%, Cr:0~1.00%、 Nb: 0-0.10%, V:0~1.00%、 Ca: 0~0.010% Al:0~1.00%、 Sn: 0~1.00%, W:0~1.00%、 Sb: 0-1.00%, Zr: 0-1.00%, and REM: 0~0.30%, The remainder comprises Fe and impurities; and A coating formed on the surface of the steel plate substrate, containing Al and Fe and having a thickness of 25 μm or more; In a cross section of the first steel member and the second steel member in the thickness direction including the spot welding area, a filler containing Al and Fe exists in a gap between the first steel member and the second steel member around the spot welding area; The filler has a cross-sectional area of ​​3.0×10 4 μm 2 and the filling rate of the gap within a range of 100 μm from the end of the plastic metal ring zone formed around the spot welding zone is 80% or more; The filler includes a first region containing, by mass%, Al: 15% to 35%, Fe: 55% to 75%, and Si: 4% to 9%; and a second region containing, by mass%, Al: 35% to 55%, Fe: 40% to 55%, and Si: 1% to 4%.

2. The joining component according to claim 1, characterized in that: The chemical composition of the steel plate base material of the first steel member contains, in mass%, one or more of Mo: 0.10 to 1.00%, Cu: 0.10 to 1.00%, and Ni: 0.10 to 1.00%. The first region further contains 0.25% or more of one or more of Mo, Cu and Ni in total content, The second region further contains 0.15% or more of one or more of Mo, Cu and Ni in total content.

3. The joining component according to claim 2, characterized in that: The average Feret diameter of the second region is 30 μm or less.

4. A method for manufacturing a joining component, characterized in that: The manufacturing method comprises: A heat treatment process, wherein the steel member is obtained by heating the coated steel plate at a heating rate of 1.0 to 1000°C / second to Ac3 point to (Ac3 point + 300)°C, and cooling the coated steel plate to a temperature below Ms point at a cooling rate above the upper critical cooling rate, wherein the coated steel plate comprises: a steel plate having a chemical composition of 0.25 to 0.65% C, 0.10 to 1.00% Si, 0.30 to 1.50% Mn, 0.050% or less P, 0.0100% or less S, 0.0100% or less N, 0.010% or less Ti, 0.010 to 0.100% B, and 0.0 005~0.0100%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1.00%, Cr: 0~1.00%, Nb: 0~0.10%, V: 0~1.00%, Ca: 0~0.010%, Al: 0~1.00%, Sn: 0~1.00%, W: 0~1.00%, Sb: 0~1.00%, Zr: 0~1.00% and REM: 0~0.30%, the remainder includes Fe and impurities, and a coating formed on the surface of the steel sheet, containing Al, and the adhesion amount is 50g / m 2 above; and a spot welding step of joining the steel member after the heat treatment step to a second steel member of a corresponding material by spot welding; In the spot welding process, The steel member and the second steel member are arranged to overlap with each other with a gap of 50 μm to 500 μm at least at a position where the current-carrying electrode is pressed; For the steel member and the second steel member, the energized electrode is pressed at a striking angle of less than 15 degrees and a pressure of more than 300 kgf, and an AC power supply of 50 Hz or 60 Hz is used to apply an upward slope with gradually increasing energization amount for more than 5 cycles, and then a molten core is formed to perform joining.

5. The method for manufacturing a joint component according to claim 4, characterized in that: The chemical composition of the steel sheet contains, in mass%, one or more of Mo: 0.10 to 1.00%, Cu: 0.10 to 1.00%, and Ni: 0.10 to 1.00%.

6. The method for manufacturing a joint component according to claim 5, characterized in that: In the spot welding step, the average cooling rate at 800 to 500° C. is set to 500° C. / sec or more.

Citation Information

Patent Citations

  • Manufacturing method for collision reinforcing material for vehicle and collision reinforcing material

    JP2002102980A

  • Aluminum plated steel sheet having excellent resistance weldability and worked parts obtained by using the same

    JP2004002932A

  • Method for spot-welding aluminum-plated steel sheet

    JP2006212649A

  • Spot welding method for alloyed aluminum plated steel sheet or press component having aluminum alloy layer

    JP2011167742A

  • Steel, and method for manufacturing the same, and steel sheet for quenching treatment

    JP2012001802A